Novel experimental methodologies to reconcile large- and small-signal responses of Hafnium-based Ferroelectric Tunnel Junctions. (February 2023) - Massarotto, Marco; Driussi, Francesco; Affanni, Antonio; Lancaster, Suzanne; Slesazeck, Stefan; Mikolajick, Thomas; Esseni, David
Abstract: Ferroelectric Tunnel Junctions (FTJs) are promising electron devices which can be operated as memristors able to realize artificial synapses for neuromorphic computing. In this work, after a thorough validation of the in-house-developed experimental setup, novel methodologies are devised and employed to investigate the large- and small-signal responses of FTJs, whose discrepancies have proven difficult to interpret in previous literature. Our findings convey a significant insight into the contribution of the irreversible polarization switching to the bias-dependent differential capacitance of the ferroelectric–dielectric stack. Highlights: Versatile experimental setup is validated for both large and small signal analyses. Triangular AC small signal helps distinguish the irreversible polarization switching. AC sinusoid over a triangular waveform can probe both large and small signal behaviour. Large and small signal responses can be split by proper filtering the overall current. Triangular frequency can link large and small signal switching capacitance peaks.